Disaffected democracies : what's troubling the trilateral countries? - Pharr, Susan J.; Putnam, Robert D. (Princeton University Press, 2000)
It is notable that as democracy replaces other forms of governing throughout the world, citizens of the most established and prosperous democracies increasingly report dissatisfaction and frustration with their governments. This volume examines why this is so.
Keywords: Honʼyaku iin shachū -- Japan; Universidad Sergio Arboleda; Democracy.; Europe -- Politics and government.; Japan -- Politics and government.; United States -- Politics and government.; Democracy; Démocratie.; Europe -- Politique et gouvernement.; Japon -- Politique et gouvernement.; États-Unis -- Politique et gouvernement.; democracy.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Politics and government; Europe; Japan; United States; Demokratie; Legitimität; Parlamentarismus; Politische Krise; Politisches System; Politikverdrossenheit; Westeuropa; Westliche Welt; USA; Democratie.; Politiek vertrouwen.; Publieke opinie.; Aufsatzsammlung.